FGA modulates immune infiltration and tumor progression via SLC7A11/xCT-mediated disulfidptosis in the tumor microenvironment of lung adenocarcinoma - Li, Gen; Li, Qiuping; Yang, Sheng; Guo, Dongmei; Tao, Yanling; Jia, Yan (Frontiers in Immunology, 2025)
Emerging evidence highlights the tumor microenvironment’s (TME) crucial role in driving tumorigenesis and malignant progression. Disulfidptosis has recently been discovered as a non-apoptotic cell death mechanism triggered by intracellular disulfide stress. However, the impact of disulfidptosis within the dynamic modulation of the immune and stromal components in the TME of lung adenocarcinoma (LUAD) remains poorly characterized. In the presented study, RNA-seq and clinical data of LUAD patients were downloaded from TCGA; screening for genes associated with disulfidptosis and immune infiltration, revealed that fibrinogen alpha chain (FGA) modulates immune infiltration via disulfidptosis regulation. We also in-vitro experiments identified FGA suppression abrogates disulfidptosis through SLC7A11/xCT downregulation and attenuated disulfidptosis while concurrently enhancing malignant phenotypes, including cellular proliferation, migratory capacity, and invasive potential in LUAD models. This study reveals that FGA functions as a tumor suppressor that can impede the tumorigenesis of LUAD by modulating xCT expression, suggesting a novel therapeutic strategy enabling modulation of disulfidptosis for LUAD management.